ANALISIS FAKTOR-FAKTOR YANG MENDORONG KINERJA DOSEN TETAP PADA FAKULTAS KOMUNIKASI DAN BISNIS UNIVERSITAS TELKOM - Andini Andini; Yahya Arwiyah; Astadi Pangarso (Universitas Bunda Mulia, 2016)
Related to the performance of the homebase lecturers at the Faculty of Communications and Business, Telkom University, in conduct the Tri Dharma Perguruan Tinggi (Three Pillars of Tertiary Education), research and community service feels lacking. That is why this research is intended to know the performance condition also to see the factors that encourage and the factors that are dominant towards the performance of fixed lecturers at the Faculty of Communications and Business in Telkom University. The method that is used in this research is descriptive analysis with factor analysis technique. The type of this research is quantitative research. The respondants in this research are the fixed lecturers at the Faculty of Communications and Business in Telkom University. The research data is obtained by distributing questionnaires towards 70 respondants and literature review. Based on the descriptive analysis result, fixed lecturers performance in the